Endocarditis due to high-level gentamicin-resistant Enterococcus faecalis. - Lee, P. Y. (BMJ Group, 1995)
We report a case of aortic valve endocarditis caused by Enterococcus faecalis highly resistant to gentamicin, which failed to respond to conventional antibiotic combination therapy. Extensive in vitro testing was required to determine an appropriate antimicrobial regimen. Despite bacteriological resolution and cardiac surgery the patient died from complications of infective endocarditis.